Low T3 Level and Prognosis of Acute Ischemic Stroke: A Comparative Analysis - Rahman, Hosne Ara; Rahman, Mahbub ur; Haque, Jasmine Ara; Sharmin, Samira; Saha, Anup Kumar (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: Neuroendocrine profile is significantly altered in acute ischemic stroke. Increasing evidences suggested that low T3 levels immediately following acute ischemic stroke is associated with greater stroke severity, higher mortality rates and poorer functional outcome. The objective of this study was to see the possible association of serum T3 level with severity of acute ischemic stroke as well as post stroke recovery. Material & Methods: It was a prospective cross sectional study. From October 2014 to June 2015 patients with acute ischemic stroke, presented within 48 hours of onset of symptoms having radiologically confirmed cerebral infarct were enrolled in this study. Blood for thyroid hormone estimation was collected within 48 hours of onset of symptom. Neurological impairment and improvement were assessed using National Institute of Health Stroke Scale (NIHSS) score together with modified Rankin Scale (mRS) on admission day and at 4 weeks post stroke follow-up visit. Result: A total 83 patients met all inclusion criteria were studied. Mean age was 63.4 ± 15.6 years (range 47-79 years). Among eighty three patients 49 (59%) had normal T3 level and rest 34 (41%) had low T3 level. Mean T3 level was 0.4 ± 0.3 ng/ml and 1.8 ±0.5 ng/ml in lowT3 and normal T3 level group respectively. Based on NIHSS scores on admission, a much higher portion of patients (73.5%) belonged to lowT3 level group fell into moderate-to-severe category while majority of patients (53.0%) fell into mild category for normal T3 level group. In post stroke follow up, about 63.2 % patients with normal T3 level showed favorable neurological functional improvement compared to 38.2% having low T3 level (Chi square=4.9, P<0.05). Conclusion: In patients with acute ischemic stroke lower T3 level elevated the risk of poor functional outcome. Bangladesh J. Nuclear Med. 18(2): 145-148, July 2015